Integrated design, simulation, and experimental validation of advanced cellular metamaterials - Novak, Nejc (Strojniški vestnik, 2025)
Cellular metamaterials offer supreme properties for engineering, medicine, and defence, but their transition to industrial use faces design, fabrication, and characterisation challenges. This review provides an overview of 20 years of advancements in cellular structures, from open-cell foams to triply periodic minimal surfaces (TPMS), presenting novel fabrication techniques (e.g., explosive compaction for UniPore structures) and demonstrating validated computational models for optimising graded auxetic and hybrid TPMS lattices. The study indicates that porosity and base material primarily govern energy absorption, with closed-cell foams and TPMS outperforming other geometries. Additive manufacturing enables spatially graded designs with tailored mechanical properties. This work accelerates the development of next-generation metamaterials for crash absorption, blast protection, and biomedical devices.
Keywords: celične strukture; cellular structures; computational simulations; eksperimentalno testiranje; experimental testing; mechanical properties; mehanske lastnosti; metamateriali; metamaterials; računalniške simulacije